KEMAMPUAN MENYELESAIKAN SOAL PISA PADA KONTEN CHANGE AND RELATIONSHIP - Helyana Teresa; Zubaidah Zubaidah; Asep Nursangaji (Jurnal AlphaEuclidEdu, 2020)
This Educators are required to be able to form a generation that can act effectively in the face of world changes that are so fast and complex. The PISA study that has been conducted has not used a sample that depicts all Indonesian students. Especially for students who are in SMP Negeri 4 Jawai not yet become a sample in the PISA study. This study aims to describe and find out how the ability to solve the Program for International Student Assessment (PISA) content on change and relationship content by junior high school students. The research method used in this research is descriptive qualitative research survey. Subjects in this study were 26 subjects. The results of the discussion showed that the ability to solve PISA questions for students was said to be still very low. This is because students have not been able to understand the problem correctly, students have not been able to identify and select relevant information because mathematical models in context are available, students have difficulty in giving arguments at every step of solving problems and drawing conclusions.